2017
DOI: 10.3945/ajcn.116.151332
|View full text |Cite
|
Sign up to set email alerts
|

Impact of breakfast skipping compared with dinner skipping on regulation of energy balance and metabolic risk ,

Abstract: Meal skipping has become an increasing trend of the modern lifestyle that may lead to obesity and type 2 diabetes. We investigated whether the timing of meal skipping impacts these risks by affecting circadian regulation of energy balance, glucose metabolism, and postprandial inflammatory responses. In a randomized controlled crossover trial, 17 participants [body mass index (in kg/m): 23.7 ± 4.6] underwent 3 isocaloric 24-h interventions (55%, 30%, and 15% carbohydrate, fat, and protein, respectively): a brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
111
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 43 publications
5
111
2
8
Order By: Relevance
“…We speculate that eTRF may have increased energy expenditure in rodents but not in humans because (1) brown fat activity is a greater fraction of energy expenditure in rodents than humans; (2) the rodents following eTRF had increased food‐seeking behaviors, which boosted their activity energy expenditure; (3) the rodents’ timing and duration of sleep differed between the eTRF and control groups; and/or (4) rodent energy expenditure was normalized by body weight rather than by fat‐free mass and fat mass, as recommended . Our data are in agreement with a prior study finding that skipping breakfast did not negatively affect 24‐hour energy expenditure but are in conflict with a second study that reported that skipping breakfast and skipping dinner both modestly increased energy expenditure, relative to eating three meals per day . However, the latter three‐arm study was only partially randomized, and there was no difference in energy expenditure between skipping breakfast and skipping dinner, which suggests that the circadian timing of food intake does not significantly affect 24‐hour energy expenditure.…”
Section: Discussionsupporting
confidence: 90%
“…We speculate that eTRF may have increased energy expenditure in rodents but not in humans because (1) brown fat activity is a greater fraction of energy expenditure in rodents than humans; (2) the rodents following eTRF had increased food‐seeking behaviors, which boosted their activity energy expenditure; (3) the rodents’ timing and duration of sleep differed between the eTRF and control groups; and/or (4) rodent energy expenditure was normalized by body weight rather than by fat‐free mass and fat mass, as recommended . Our data are in agreement with a prior study finding that skipping breakfast did not negatively affect 24‐hour energy expenditure but are in conflict with a second study that reported that skipping breakfast and skipping dinner both modestly increased energy expenditure, relative to eating three meals per day . However, the latter three‐arm study was only partially randomized, and there was no difference in energy expenditure between skipping breakfast and skipping dinner, which suggests that the circadian timing of food intake does not significantly affect 24‐hour energy expenditure.…”
Section: Discussionsupporting
confidence: 90%
“…In a study using data from NHANES 2005-2010, Kant and Graubard [65] report that the difference in calories in a 24-hour period, comparing a day with breakfast and a day without, was 247 and 187 kcal, respectively, and that energy intake at lunch was higher on the day without breakfast (202 kcal in men and 121 kcal in women), showing a caloric compensation behavior at lunchtime. Using a randomized controlled trial design, Nas et al [66] showed that subjects who do not have breakfast have higher postprandial insulin concentrations after lunch and an increase in fat oxidation during the day compared to subjects who do not consume dinner, which suggests the development of a metabolic inflexibility in response to a prolonged fast that, in the long term, can lead to low-grade inflammation and an altered glucose homeostasis. These studies show compensatory eating behavior at lunchtime in those subjects who do not consume breakfast, which may lead to metabolic risks.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, reduced intake at dinner was found to be protective against obesity and metabolic syndrome . One recent prospective study found that prolonging the duration of night‐time fasting could be beneficial for reducing the risk of recurrence among breast cancer survivors, whereas a recent RCT found that prolonging the duration of night‐time fasting by breakfast skipping increased the inflammatory potential of peripheral blood cells . However, none of these studies linked circadian nutritional behaviours directly with cancer risk.…”
Section: Introductionmentioning
confidence: 99%